Assessing the Impact of Mobile Money in Providing Financial Inclusion for the Rural Population of the Kasena/Nankana West District of Upper East Region - Baako, Emmanuel (2017)
A Dissertation presented to the Department of Economic in partial fulfillment of the requirement for the Award of the Degree of Master of Science in Economics,